The effect of educational intervention based on the health belief model on knowledge, attitude, and function of women about Pap smear test at Iranian health centers: A randomized controlled clinical trial - Elahe Samami; Seyed Jalil Seyedi- Andi; Beyrambibi Bayat; Davoud Shojaeizadeh; Neda Ahmadzadeh Tori (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND AND OBJECTIVE: This study aimed to examine the effect of educational intervention using the health belief model on knowledge, attitude, and function of women about Pap test at health centers. METHODOLOGY: This randomized controlled clinical trial was conducted on 120 women who were allocated into two groups (intervention = 60 and control = 60). The sampling method was a multistage cluster. The training was provided in two sessions for 90 min. Data gathering tool was a 4-part researcher-made questionnaire including demographic characteristics, knowledge, health belief model structures, and function. Women were evaluated and completed the questionnaire in two stages (before and 2 months after training). Data were analyzed by Kolmogorov-Smirnov, Wilcoxon, linear regression, Mann-Whitney U-test, Fisher, Chi-square, and marginal homogeneity tests. RESULTS: At baseline, there was no significant difference between the groups regarding the mean of knowledge and the structures of health belief model scores. The average scores of participants in terms of health belief model structures were increased significantly after the training sessions. Furthermore, the comparison of the performance of Pap smear before training showed that in the intervention group (23.3%) and in the control group (31.7%), there was no significant difference in terms of the history of performing the Pap smear test (P = 0.414). However, a significant difference (P = 0.001) was observed after training in the intervention group (31.7%) and in the control group (3.3%). CONCLUSION: Educational intervention using the health belief model is effective in increasing knowledge, attitude, and function of women in terms of providing useful and required education.